Choosing a breast reconstruction method when planning radiotherapy in breast cancer patients - I. M. Onofriychuk; A. D. Zikiryakhodzhaev; E. K. Saribekyan; D. R. Ortabaeva; M. Yu. Vlasova; T. S. Berestok (ABV-press, 2023)
The list of indications to adjuvant radiation therapy for breast cancer patients was extended in recent years, regardless of the type of reconstruction. Surgeons and radiologists have to choose the most appropriate sequence of reconstruction and to reduce the risk of complications. Radiotherapy is one of the main factors causing complications in patients undergoing breast reconstruction, and vice versa, the implant might hinder radiotherapy, preventing proper delivery of the required radiation dose. Both oncologists and radiologists try to reduce the incidence of complications, which is an important interdisciplinary aim. This article investigates international experience of well-known cancer centers and experience of the Department of Oncology and Reconstructive Breast and Skin Surgery, P.A. Herzen Moscow Oncology Research Institute, a branch of the National Medical Radiology Research Center, Ministry of Health of Russia. We analyzed the choice of the breast reconstruction method in patients undergoing radiotherapy after surgery and developed recommendations for choosing an optimal method of reconstructive surgery.